Duplications and functional convergence of intestinal carbohydrate-digesting enzymes - Brun, Antonio (2020)
Vertebrate diets and digestive physiologies vary tremendously. Although the contribution of ecological and behavioral features to such diversity is well documented, the roles and identities of individual intestinal enzymes shaping digestive traits remain largely unexplored. Here, we show that the sucrase-isomaltase (SI)/maltase-glucoamylase (MGAM) dual enzyme system long assumed to be the conserved disaccharide and starch digestion framework in all vertebrates is absent in many lineages. Our analyses indicate that independent duplications of an ancestral SI gave rise to the mammalianspecific MGAM, as well as to other duplicates in fish and birds. Strikingly, the duplicated avian enzyme exhibits similar activities to MGAM, revealing an unexpected case of functional convergence. Our results highlight digestive enzyme variation as a key uncharacterized component of dietary diversity in vertebrates.